Development of a fall prevention device for older persons - Abdul Rahman, K.; Ahmad, S. A.; Wada, C.; Ashari, A.; Che Soh, A.; Gopalai, A. A.; Murugasen, S. (International Society of Gerontechnology, 2022)
The ever-increasing ageing population has raised awareness globally. The deterioration of health among older persons commonly leads to an increased risk of falling. The desire to live independently has the consequences for them and society as well. Enabling environments for older persons can be created, easing the social challenge of preparing for an ageing society while improving quality of life in their golden years. Technology solutions have been a game-changer supporting the families as the default caretakers for ageing relatives, bringing peace of mind. Fall detection systems represent one of the assistive technologies for older persons, as they can offer immediate assistance in case of emergency. Albeit the usage of the device is statistically low in Malaysia, they have been known to save lives (Bourke et al., 2010). Studies regarding fall detections and balance intervention have resulted in increasing safety, improving gait and physical activities (Lin & Wai, 2021; Hsieh et al., 2018). This study aims to improve the device by incorporating balance monitoring system, delivering better care for older persons. Rather than simply detecting falls, the proposed system will monitor balance instability, alerting the user to predict future falls and therefore serving as a fall prevention device.